The Effect of Financial Performance on Market to Book Value of Equity (MBVE) in LQ45 Companies on the IDX Post Pandemi Covid 19 - Lia Febriani; Agus Sukoco (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to test and prove whether financial performance affects the market to book value of equity (MBVE). The population in this study are all LQ45 companies listed on the IDX for the 2019-2021 period. Sampling was carried out by purposive sampling and 135 companies were selected. The data in this study come from secondary data obtained through documentation techniques. Data analysis with multiple regression partially using SPSS. The results showed that simultaneously there was a significant effect of CR, DER, and ROA on MBVE. Based on partial testing, it is concluded that CR, DER and ROA have a significant effect on MBVE.